Self-Perception of Physical Function Contributes to Participation in Cognitively- and Physically-Demanding Activities After Stroke - Nicholas, Marjorie L.; Burch, Kari; Mitchell, Julianne R.; Fox, Annie B.; Baum, Carolyn M.; Connor, Lisa Tabor (Frontiers in Neurology, 2020)
Background: Persons with and without aphasia experience decreased participation in meaningful activities post-stroke that result in reduced autonomy and poorer quality of life. Physical, cognitive, and/or communication deficits are prevalent post-stroke and many activities given up are purported to require high levels of communicative, cognitive or physical skill. However, the relationship between deficits after stroke and participation in life activities that require high skill levels in these three areas has not been investigated fully. Objectives: The objectives of this study are to: 1) determine differences in reported participation in communicatively-, cognitively-, or physically-demanding activities in persons after stroke with and without aphasia living in the community, and 2) investigate whether performance on commonly used self-perception assessments of these three areas predicts reported participation in activities requiring higher levels of skill in these domains. Methods: In a cross-sectional design, 82 individuals at least 6 months post-stroke with (N=34) and without aphasia (N=48) were administered a battery of neuropsychological and participation-based assessments. Supported communication techniques maximized inclusion of individuals with aphasia. Regression analyses investigated the relationship between self-perceived communicative, cognitive, and physical functioning and reported participation in activities post-stroke that required high amounts of skilled function in these areas. Results: People with and without aphasia did not differ in the percentage retained in communicatively-, cognitively-, or physically-demanding activities. All individuals retained higher levels of participation in communicatively- and cognitively-demanding activities (at least 60% retained), compared to participation in physically-demanding activities (about 50% retained). The strongest predictor for retaining participation in two of the three domains of activities was self-perception of physical function, though much of the variance remained unexplained. Self-perception of communication was not related to participation retention in any of the three domains. Significance of Impact: Rehabilitation professionals should be aware of the impact that a variety of communicative, cognitive, and physical factors may have on participation post-stroke. Self-perceptions of impairments in communication and cognition may not directly predict participation in activities requiring high levels of communicative and/or cognitive skill, at least for those with mild impairment, even though activities requiring those skills are given up or done less after stroke.